The Language of Thought and The Embodied Nature of Language Use. - Teng, Norman Yujen (Philosophical Studies, 1999)
This article focuses on the language of thought and language use. Jerry A. Fodor's language of thought (LOT) hypothesis, focusing on his contention that the systematicity of language use provides a solid ground for the LOT hypothesis. The usual response to Fodor's systematicity arguments is to argue that systematicity is much less than Fodor assumes. And the sort of systematicity that Fodor draws the attention to is a language based artifact constructed from a toplevel task analysis of what a cognitive system does.